Systems engineering an approach to information-based design - Hazelrigg, George A. (Prentice Hall international series in industrial and systems engineering., 1996)
While being an experiment within itself to teach normative design theory, this comprehensive book treats engineering design as a decision-making process, which it is, from a quantitative point of view. This opens a host of well-developed methods to application, including a mathematically rigorous treatment of risk and uncertainty in design. The book is designed to assist the reader by defining the boundaries of a discipline, providing order for the learning process, and assisting the reader in self testing. Provides a number of new methods and aids to engineering design: Cartoons for identifying system options; Scenario Diagrams for system simulation; an approach to the measurement of information relating to specific decisions; an overall and general approach to engineering design; a rigorous treatment of risk and uncertainty in engineering design, including measures of system value that are valid under risk and uncertainty; and an explanation of the principles of game theory as applied to engineering design.